Endocrinopathies in adolescents with thalassaemia major receiving oral iron chelation therapy. (2nd January 2016) - Sharma, Rajni; Seth, Anju; Chandra, Jagdish; Gohain, Suraj; Kapoor, Seema; Singh, Pratiksha; Pemde, Harish
Abstract : Background: Endocrinopathies are common in patients with thalassaemia major (TM) despite parenteral iron chelation therapy with deferoxamine. There are only a few studies on the efficacy of oral deferiprone in preventing endocrine dysfunction. Aim: To determine the growth and endocrine complications in children with TM receiving oral iron chelation with deferiprone. Methods: All adolescents with TM receiving regular blood transfusion and deferiprone were evaluated prospectively for growth and pubertal status over a 1-year period. Tests for endocrine function included oral glucose tolerance test, calcium, phosphate, alkaline phosphatase, parathyroid hormone and thyroid profile and, in those with delayed/arrested puberty, sex steroids and gonadotropins. Clonidine-stimulated growth hormone (GH) was measured in patients with height ≤−3 SD. Results: 89 patients [51 males, 38 females, mean (SD) age 13·6 (2·5) years] were evaluated. Mean (SD) pre-transfusion haemoglobin was 9·2 (1·1) g/dl and the mean (SD) age of starting deferiprone was 5·1 (2·4) years. Mean (SD) ferritin was 9159 (3312) pmol/L (normal <2247). 49 (55%) subjects were of short stature and 25 (27%) had a height Z-score ≤ −3. GH testing was performed in 19 patients, of whom 17 had peak GH values <10 μg/L. Delayed puberty and/or hypogonadism was present in 54·1% patients at or beyond the age of normal puberty. Impaired glucose tolerance/diabetes mellitus, hypoparathyroidism and primary hypothyroidism (subclinical) were present in 13·0%, 10·1% and 8·9%, respectively. Overall, 44 (49·4%) adolescents had at least one endocrinopathy. Conclusion: Adolescents with TM on oral iron chelation therapy with deferiprone experienced a high prevalence of growth faltering and endocrinopathies which was comparable to that previously reported with deferoxamine. A combination of deferoxamine and deferiprone may be necessary to prevent growth and endocrine problems.